1996
DOI: 10.1104/pp.111.2.577
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Sequence Tags of Chinese Cabbage Flower Bud cDNA

Abstract: We randomly selected and partially sequenced cDNA clones from a library of Chinese cabbage (Brassica campestris L. ssp. pekinensis) flower bud cDNAs. Out of 1216 expressed sequence tags (ESTs), 904 cDNA clones were unique or nonredundant. Five hundred eighty-eight clones (48.4%) had sequence homology to functionally defined genes at the peptide level. Only 5 clones encoded known flower-specific proteins. Among the cDNAs with no similarity to known protein sequences (628), 184 clones had significant similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 25 publications
(48 reference statements)
6
35
1
1
Order By: Relevance
“…In addition to the demonstration of homologous sequences in Antirrhinum described here, related proteins have been identified in Betula verrucosa (Engel et al, 1997;Twardosz et al, 1997), Olea europaea (Batanero et al, 1997), Artemisia vulgaris (Engel et al, 1997), Cynodon dactylon (Knox et al, 1992), Phleum pratense, and Lilium longiflorum (Engel et al, 1997;Twardosz et al, 1997), and multiple types were identified in Brassica rapa and B. napus (Toriyama et al, 1995;Lim et al, 1996) during the course of this study. The partial amino acid sequence from the second pollen protein purified in this study, PP-A, indicates that it, too, is a member of this protein family.…”
Section: Discussionsupporting
confidence: 59%
“…In addition to the demonstration of homologous sequences in Antirrhinum described here, related proteins have been identified in Betula verrucosa (Engel et al, 1997;Twardosz et al, 1997), Olea europaea (Batanero et al, 1997), Artemisia vulgaris (Engel et al, 1997), Cynodon dactylon (Knox et al, 1992), Phleum pratense, and Lilium longiflorum (Engel et al, 1997;Twardosz et al, 1997), and multiple types were identified in Brassica rapa and B. napus (Toriyama et al, 1995;Lim et al, 1996) during the course of this study. The partial amino acid sequence from the second pollen protein purified in this study, PP-A, indicates that it, too, is a member of this protein family.…”
Section: Discussionsupporting
confidence: 59%
“…A full-length cDNA clone encoding a putative type IIB Ca 2 ϩ -ATPase was isolated from a soybean hypocotyl cDNA library by using a partial cDNA clone (F955) that encodes another putative Ca 2 ϩ pump from Brassica (Lim et al, 1996). For this gene, named SCA1 , the cDNA sequence showed an open reading frame of 3042 bp that encodes a polypeptide (SCA1p) with a molecular mass of 110.4 kD (Figure 1).…”
Section: Primary Structure Of Sca1pmentioning
confidence: 99%
“…The F955 clone was a partial cDNA that encoded a putative plasma membrane-type Ca 2ϩ -ATPase isolated from Brassica flower bud cDNA (Lim et al, 1996). Positive plaques from the primary screening were purified by two additional rounds of plaque hybridizations.…”
Section: Isolation Of Ca 2؉ -Atpase Cdna From Soybean Cdna Library Anmentioning
confidence: 99%
“…The concept of using cDNAs as a route to expedite gene discovery was first demonstrated in the early 1980s (Putney et al 1983). Later gene discovery in most plants was done primarily by sample sequencing of expressed sequence tags (ESTs) (Lim et al 1996;Covitz et al 1998).…”
Section: Introductionmentioning
confidence: 99%